Rectal foreign body of a shattered glass bottle; Case report of unexpected late post-operative hemorrhage managed transanally. (2020) - Klein, Elliot; Bressler, Moshe; Nadler, Shmuel; Shayowitz, Michelle; Lapin, Seth
Highlights: Colonoscopy post perforating rectal injury may be employed to evaluate and treat bleeding. DRE should be cautioned when suspecting hazardous material in the colorectal tract. Mobilization of foreign bodies must be determined in a case by case basis. Abstract: Introduction: Retained rectal foreign bodies are commonly implicated in patients engaging in erotic behavior. The foreign bodies vary widely, however, penetrating rectal wounds are uncommon and often complicate the retrieval of the object. The rich vascular bed of the rectal mucosa provides additional bleeding complications. Presentation of case: A 55-year-old male presented with active bleeding after intentional insertion of a glass bottle into the rectum which shattered. Partial retrieval via proctoscopy was followed by an exploratory laparotomy with a diverting colostomy, mucous fistula, and presacral drainage. Postoperative course was complicated by severe hematochezia. Colonoscopy was performed in the operating room found actively bleeding ulcers at sites of previously lacerated mucosa; one pulsating, protruding, vessel was visible. Clips were placed over the vessel with cessation of bleeding. Barium enema at three months follow revealed no leaks allowing for reversal of the colostomy. Discussion: This case of operative retrieval of a rectal foreign body is unique because it displays deviation from commonly used algorithms are periodically needed to optimize patient recover. Conclusion: The utilization of minimally-invasive colonoscopy prior to additional surgical intervention in post-operative rectal bleeding following a rectal foreign body retrieval may improvie patient recovery time, functionality, and long-term outcomes.